Comic Strip Writing Errors in Simple Past and Past Continuous Tenses in Veterinary Students - Nur Laily Lupita Sari; Gadis Kartika Pratiwi (Jurnal Vokasia, 2026)
This study investigates grammatical errors in the use of Simple Past and Past Continuous tenses among veterinary vocational students in comic strip writing tasks. Grammatical competence plays a crucial role in effective communication; however, many English as a Foreign Language (EFL) learners experience difficulties in applying tense forms consistently in contextualized writing. The aim of this study is to identify the types and patterns of errors produced by students and to examine how comic strip tasks function as a medium for revealing learners’ grammatical competence. The study employed a descriptive qualitative design with quantitative support using an error analysis approach. The data were collected from students’ written dialogues in veterinary-themed comic strips and analyzed based on error classification frameworks. The findings reveal that tense inconsistency is the most dominant error pattern, particularly the shift between past and present forms within the same narrative. In addition, students demonstrated confusion in verb form selection, limited ability to use Past Continuous meaningfully, and difficulties in sentence structure, especially in question formation. The results also indicate that comic strip writing serves not only as a learning medium but also as an effective diagnostic tool for identifying authentic grammatical weaknesses. Overall, the study suggests that grammar instruction in ESP contexts should emphasize contextualized and meaningful language use rather than isolated rule memorization.